Correspondents and Professional Standards in News Coverage (A Field Study) - خزعل, عبد النبي (ALBAHITH ALALAMI, 2015)
The essence of the new work in the satellite TV channels is to provide news coverage of news that will inform the people of what is going on around them in order to increase their political, social, economic and cultural awareness and this drives them to take positions or certain behaviors on according to what the communicator in these channels wants. News and news reports are generally used as a psychological variable to influence public opinion and does not offer interestingness and information. Therefore, satellite TV channels have assumed special attention towards their correspondents desiring to achieve scoop in news coverage and to have the final word in reading events and install its private destinations. Recognizing the fact of intense competition between them and similar satellites TV channels of the same band and in the middle of this news activity the correspondents of Iraqi satellite channels work with professionalism in their news treatment in accordance with the rules of news correctness, its accuracy, and objectivity on one hand and business requirements for media administrations with liberalization policies or strict directives. And among all of these, Iraqi reporters work in political, security, social and even legislative environments. They hinder the freedom of their media movement and limiting their ability to express an opinion freely. The results of the research analysis can be summarized as follows: